Her hometown is not where she lives, but a Tunisian island - Temzini, Lina (Youth Journalism International, 2019)
Djerba, TUNISIA – My hometown Guellala is a place of wonders, where love, compassion and kindness prevail. It’s a place that means so much to me, and even though I have never actually lived there, I think of it as home. It’s a small town on the beautiful island of Djerba, an island located off […]
Keywords: Récits de voyage -- Djerba